Data on the densification during sintering of binder jet printed samples made from water- and gas-atomized alloy 625 powders - Amir Mostafaei (Data in Brief, 2017)
Binder jet printing (BJP) is a metal additive manufacturing method that manufactures parts with complex geometry by depositing powder layer-by-layer, selectively joining particles in each layer with a polymeric binder and finally curing the binder. After the printing process, the parts still in the powder bed must be sintered to achieve full densification (A. Mostafaei, Y. Behnamian, Y.L. Krimer, E.L. Stevens, J.L. Luo, M. Chmielus, 2016; A. Mostafaei, E. Stevens, E. Hughes, S. Biery, C. Hilla, M. Chmielus, 2016; A. Mostafaei, Y. Behnamian, Y.L. Krimer, E.L. Stevens, J.L. Luo, M. Chmielus, 2016) [1–3]. The collected data presents the characterization of the as-received gas- and water-atomized alloy 625 powders, BJP processing parameters and density of the sintered samples. The effect of sintering temperatures on the microstructure and the relative density of binder jet printed parts made from differently atomized nickel-based superalloy 625 powders are briefly compared in this paper. Detailed data can be found in the original published papers by authors in (A. Mostafaei, J. Toman, E.L. Stevens, E.T. Hughes, Y.L. Krimer, M. Chmielus, 2017) [4].